Immortalise - Mullins, Charlotte 1972- (The New Art Gallery Walsall, 2018)
Immortalise' celebrates the work of Walsall artist Andrew Tift (b.1968), Winner of the BP Portrait Award in 2006. This lavishly illustrated publication brings together brand-new work combined with selected works from the artist's past practice, comprising paintings, drawings, photography and sketchbooks. Focusing around the genre of portraiture, it testifies to the richness and breadth of his practice and includes commissioned portraits, personal projects with specifically chosen sitters and more experimental work in which Tift has challenged himself both technically and conceptually, pushing the boundaries of portraiture and reflecting on themes such as the cycles of life, presence and absence, the passing of time and the persistence of memory
Published in conjunction with the exhibition "Andrew Tift - Immortalise", 25 May - 2 September 2018, The New Art Gallery Walsall. - Includes bibliographical references (page 18)
Keywords: Tift, Andrew -- 1968-; Geschichte 1994-2017; Porträtfotografie; Bildnismalerei; Bildnis; Tift, Andrew / Exhibitions; Ausstellungskatalog -- The New Art Gallery Walsall -- 25.05.2018-02.09.2018 -- Walsall; Bildband